Philosophical and Pedagogical Conception of V. Zenkovskyi (dedicated to 130-anniversary of Zenkovskyi’s birth) - Predborska, Iryna (Filosofiya osvity. Philosophy of Education, 2011)
The author of the given article actualizes the philosophical and pedagogical conception of V. Zenkovskyi in the context of the philosophy of education’s contemporary tendencies. She analyzes how philosopher postulates the main ideas of humanistic pedagogy, person-oriented education, according to which the construction of educational strategies begins from cognition of child’s inner intentions, his/her inner life; and how the main task of pedagogical efforts is directed to search the ways of combination in child’s soul the freedom with good, with moral values of mankind.